2018
DOI: 10.1016/j.ccell.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis Identifies Four Molecular and Clinical Subsets in Uveal Melanoma

Abstract: In the originally published version of this paper, there were two instances in which a paper by Raab et al. was cited, but the full reference was accidentally omitted from the reference list. First, in the subsection titled ''Arid1a Haploinsufficiency Alters Global Chromatin Occupancy and Metastasis Genes,'' paragraph 4, the authors wrote, ''To determine if these genes have direct interactions with ARID1A and SWI/SNF components in human HCC, we examined ChIP-seq experiments from HepG2 cells performed by Raab e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
467
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(524 citation statements)
references
References 1 publication
31
467
9
1
Order By: Relevance
“…Chang and colleagues reported that class 2 UM is strongly associated with genes upregulated in primitive neuroectodermal cells (Chang et al 2008). In support of this, nestin mRNA expression was identified in a panel of genes associated with time to metastasis both from the data generated by The Cancer Genome Atlas (TCGA) and also from their analysis of gene expression data previously generated by Laurent et al, although this association was not found to be significant when examining the hazard ratio and 95% CI (Laurent et al 2011;Robertson et al 2017). Of interest in our current study was the absence of nestin positivity in normal choroidal melanocytes as compared to its presence in UM cells, which may suggest reversion to a more primitive phenotype following UM cell transformation.…”
Section: Discussionmentioning
confidence: 90%
“…Chang and colleagues reported that class 2 UM is strongly associated with genes upregulated in primitive neuroectodermal cells (Chang et al 2008). In support of this, nestin mRNA expression was identified in a panel of genes associated with time to metastasis both from the data generated by The Cancer Genome Atlas (TCGA) and also from their analysis of gene expression data previously generated by Laurent et al, although this association was not found to be significant when examining the hazard ratio and 95% CI (Laurent et al 2011;Robertson et al 2017). Of interest in our current study was the absence of nestin positivity in normal choroidal melanocytes as compared to its presence in UM cells, which may suggest reversion to a more primitive phenotype following UM cell transformation.…”
Section: Discussionmentioning
confidence: 90%
“…KDM6A (also known as UTX) is a core component of the ‘complex of proteins associated with SET1’ (COMPASS) and it has been shown to require BAP1 for its recruitment at chromatin enhancers . Inactivation of those genes has been reported to occur through different mechanisms, ranging from DNA methylation to complex DNA rearrangements , which can be missed by targeted DNA sequencing. IHC is a reliable method to assess the status of BAP1 , while IHC for KDM6A has been recently used to assess the status of KDM6A in PDAC .…”
Section: Resultsmentioning
confidence: 99%
“…BAP1 and KDM6A have been shown to interact at chromatin enhancers and disruption of this functional interaction in cancers drives malignancy through a mechanism that can be pharmacologically targeted . Inactivation of those genes has been reported to occur through different genetic and epigenetic mechanisms , which can be missed by targeted DNA sequencing approaches and often lead to the loss of functional proteins. In our cohort of SPNs, we found that a lack of or reduced expression of both KDM6A and BAP1 is enriched in metastatic cases, suggesting that their function is a barrier to the development of metastatic disease at least in a subset of SPNs.…”
Section: Discussionmentioning
confidence: 99%
“…in uterine carcinosarcoma) or variant morphology (e.g. squamous or neuroendocrine differentiation in urothelial bladder carcinoma) . These facets are of undoubted importance, both for quality control of the analysed data, and to provide morphological correlates to molecular findings that might assist in translating molecular findings to clinical diagnostics.…”
Section: Limitations Of Tcga and Pancancer Analysis Projectsmentioning
confidence: 99%